Factors influencing users’ satisfaction with online agricultural products in China’s first and second-tier cities under the epidemic - Wu, Xingyuan; Aida Idris; Nur Jannah Bukhari (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Covid-19 crisis brought with it significant changes to human lives including changes to behaviour. Particularly, the Coronavirus lockdowns and other restrictions contributed to the rise of online shopping for agricultural products in China’s first and second-tier cities. The core aim of the investigation is to evaluate the factors that influence the satisfaction of users with online agricultural products in first and second-tier cities in China during the pandemic. The research methodology is qualitative and relies on interpretivism to examine the experiences regarding the satisfaction of users with online agricultural products in first and second- tier cities in China during the crisis. An inductive approach is applied and the specific data collection instrument in this research entails semi-structured interviews to facilitate a comprehensive inquiry and gain rich insights. Semi-structured interview sessions are conducted with 30 participants including Chinese shoppers who used online agricultural products between 2019 and 2022 just before the Covid-19 crisis or during the pandemic. The research findings indicate that optimism was found to be crucial to the increased consumption of online agricultural products and high quality emerged as the most influential factor behind users’ satisfaction with online agricultural products. However, online agricultural product sellers in China need to ensure excellence in their operations to succeed in the competitive online marketplace. Conclusively, this investigation achieved its overarching aim of evaluating the factors that influence the satisfaction of users with online agricultural products in first and second-tier cities in China during the pandemic.